Diagnosis aneurysm vein of Galen and ischemic brain damage by Doppler ultrasound: A CASE REPORT - Díaz Lazo, Hubertino (2015)
We report a case of a baby born at 41 weeks of gestational age who presented a Galen vein aneurysm (GVA) associated with periventricular leukomalacia and ventriculomegaly and diagnosed by Doppler color cerebral ultrasound. Ultrasound showed a 35 x 26 x 30 mm cystic lesion at the frontoparietal level of the interhemispheric midline. In addition, the newborn had Down syndrome with cardiomegaly, interatrial communication, heart failure, respiratory failure, and severe hepatomegaly. He died at 2 days of life. Pathology findings confirmed GVA. We highlight the importance of the Doppler study in a prompt diagnosis in order to initiate an early treatment with the aim of improving life expectancy.